INTERVENSI PSIKOLOGIS PADA SISWA GENERASI ALPHA JENJANG SEKOLAH DASAR YANG MENJADI KORBAN KEKERASAN SEKSUAL DI KOTA BEKASI - Pradana, Galang Putra Yudha; Siburian, Denis Natalia; Munthe, Adelia Melenia; Muntu, Livia Swita; Saputra, Nawi; Aryanto, Sani (Journal of Professional Elementary Education, 2025)
Sexual violence against elementary school children has severe impacts on psychological, social, and educational aspects. This study explores caregivers’ understanding of Trauma-Informed Care (TIC) principles, identifies trauma factors, and examines perceptions of TIC-based interventions in elementary schools. A qualitative case study approach was applied through in-depth interviews, observations, and documentation, analyzed thematically with NVivo 12. The findings show that teachers and principals emphasize physical safety, psychologists highlight emotional support and continuity, the Child Protection Agency (KPAD) stresses transparency and cross-sector collaboration, while parents focus on home-based support. Trauma is understood as the interaction between traumatic experiences, children’s emotional symptoms, and lack of environmental support. Perceptions of intervention emphasize collaborative, sustainable, and participatory approaches. In conclusion, TIC can serve as a strategic framework for preventing and addressing child trauma and is recommended to be integrated into child-friendly school policies.